Talent identification, detection and development of youth football players - sociological considerations - Richardson, D. J.; Reilly, T. (2001)
Over the years the search to identify and develop specific "talent" characteristics in order to facilitate the production of elite sporting individuals has been a significant research interest in each discipline of sports science. A limitation to this effort has been that each discipline has tended to be constrained within its own boundaries. The sociological considerations of the "talent map" have been secondary to the conventional laboratory based scientific disciplines. Certain talent characteristics may be innate or subject to the effect of training, but potential talent can not be nurtured without the appropriate environmental and support mechanisms. In recent years the emphasis on talent development within association football in the United Kingdom has increased due to the influx of international players, the inflated wage demands and the spiralling transfer fees. This review provides an overview of the sociological considerations that may impact on the development of talented young football players in the United Kingdom. The diversity of sociological considerations is implicit, as variables such as readiness, the influence of significant others, the environment, culture, socio-economic status, social mobility, intelligence and even luck are explored. Moreover, the need to recognise these considerations in conjunction with the more traditional physiological, physical and psychological talent predictors in order to promote a more holistic understanding of talent development is emphasised.